The risk associated with concomitant procedures performed during adult congenital heart surgery. (8th September 2015) - Mori, Makoto; Rosenblum, Joshua M.; Book, Wendy; Oster, Matt; Kogon, Brian
Abstract: Background: Adult patients with CHD often require complex operations, and indications for particular aspects of the operation are sometimes unclear. The aims of our study were as follows: to characterise concomitant procedures performed during adult congenital cardiac surgery, and to better define the risk involved with performing concomitant procedures during a single operation. Methods: We retrospectively studied 458 adult congenital cardiac surgical patients. Major procedures were characterised as aortic, mitral, pulmonary, tricuspid, septal defect, single ventricle, transplant, and others. We constructed logistic regression models to assess the risk for mortality, major adverse event, and prolonged length of stay. Results: A total of 362 operations involved a single major procedure, whereas 96 involved concomitant procedures. Performing concomitant procedures increased mortality (7.3 versus 2.5%), major adverse events (21.8 versus 14.9%), and prolonged length of stay (29.2 versus 17.1%). The added risks of concomitant procedures on mortality, major adverse event, and prolonged length of stay were 2.9 (95% CI 1.0–8.5, p=0.05), 1.9 (95% CI 1.1–3.3, p=0.02), and 2.4 (95% CI 1.4–4.1, p=0.003), respectively. There were 200 patients with conotruncal anomalies who underwent pulmonary valve surgery. In this subset, the added risks of concomitant procedures in addition to pulmonary valve surgery on mortality, major adverse events, and prolonged length of stay were 6.6 (95% CI 1.2–37.3, p=0.03), 2.8 (95% CI 1.2–6.6, p=0.03), and 3.3 (95% CI 1.5–7.4, p=0.005), respectively. Conclusion: Concomitant procedures performed during adult congenital heart surgery increase risk. Awareness of this risk may improve surgical decision making and outcomes.